In Vitro Evaluation of Increasing Avibactam Concentrations on Ceftazidime Activity against Ceftazidime/Avibactam-Susceptible and Resistant KPC-Producing Klebsiella pneumoniae Clinical Isolates - Marta Palombo; Benedetta Secci; Federica Bovo; Milo Gatti; Simone Ambretti; Paolo Gaibani (MDPI AG, 2023)
The novel β-lactam/β-lactamase inhibitor combinations (βL-βLICs) are one of the last-line resources available against multidrug-resistant (MDR) Gram-negative bacteria. Among βL-βLICs, ceftazidime/avibactam (CAZ-AVI) demonstrated strong activity against carbapenem-resistant Enterobacterales (CRE). Avibactam was proven to restore bactericidal activity of ceftazidime, inhibiting both KPC and OXA-48-like β-lactamases. Despite this, emergence of CAZ-AVI-resistant strains in Enterobacterales has been reported. Herein, we evaluated the in vitro ceftazidime activity in the presence of increasing concentrations of avibactam by the broth microdilution method against CAZ-AVI-susceptible and resistant genome-characterized KPC-producing K. pneumoniae (KPC-Kp) clinical isolates. Strains expressing KPC and co-expressing KPC/OXA-181 carbapenemase were selected on the basis of the different phenotypic traits for novel βL-βLICs and cefiderocol. Notably, avibactam at 8 mg/L maintained the MIC of ceftazidime above the clinical breakpoint in 14 out of 15 (93%) KPC-Kp resistant to CAZ-AVI. A high concentration of avibactam (i.e., 64 mg/L) is required to observe a bactericidal activity of ceftazidime against 9 out of 15 (60%) CAZ-AVI-resistant isolates. In vitro evaluation showed that with the increase in the concentration of avibactam, ceftazidime showed high activity against CAZ-AVI-susceptible strains. High concentrations of avibactam in vivo are required for ceftazidime to be active against CAZ-AVI-resistant KPC-Kp.